Strategic marketing - Cravens, David W. 4 0 16; Piercy, Nigel; 5 (New York : McGraw-Hill, 2009)
Designed around the marketing strategy process with a clear emphasis on analysis, planning, and implementation, this text and casebook discusses the concepts and processes for gaining a competitive advantage in the marketplace. The new edition of Strategic Marketing uses a decision-making process to examine the key concepts and issues involved in analyzing and selecting strategies. Marketing strategy is considered from a total business perspective, examining marketing strategy beyond the traditional emphasis on marketing functions. The length and design of the book offer flexibility in the use of the text material and cases. New features and updated cases have made this text the most relevant text in the market today.--publisher website.
b
Includes bibliographical references and indexes.
Keywords: 2 -- 0; 6; Decision making.;Management.;Management -- Marketing;Marketing;Marketing -- 20 -- Case studies; 20; 2